The distribution pattern of algal flora in saline lakes in Kambalda and Esperance, Western Australia - Handley, Michelle Anne (Curtin University, 2003)
The study has attempted to characterise the physicochemical limnology and distribution of algal flora of two salt lake systems in Western Australia, one from the coastal Esperance region and the other from the inland Kambalda region. Climatic conditions, water regimes and physicochemistry were found to differ markedly between the two lake systems and a total of 171 algal taxa, representing five divisions, were recorded. Of these, 82 were members of Bacillariophyta, 48 of Cyanophyta, 33 of Chlorophyta, two of Euglenophyta and six of Dinophyta. The physical limnology of salt lakes in the Esperance region was seasonally variable, defined by climatic conditions. As such, the lakes investigated in the region exhibited a stable cycle of filling during winter and spring, and drying out in summer. Four of the lakes in the region could be classified as near-permanent, and one as seasonal on the basis of predictability and duration of filling. Seasonal fluctuations in water depth resulted in fluctuations in salinity levels. Salinity levels ranged from subsaline to hypersaline, and all the lakes in the region were alkaline. In addition, the lakes were well mixed in terms of oxygen and temperature, and were impacted by eutrophication from their catchments. They were either mesotrophic or eutrophic with respect to both nitrogen and phosphorus. In geological terms, lakes in the Esperance region were separated only recently from the ocean, and two lakes retain a connection with marine waters, one through a creek during years of high rainfall and one through hydrological interactions with groundwater of marine origin. In general, the algal communities of lakes in the Esperance region were similar to those of other Australian coastal salt lakes.Diatoms and cyanobacteria were dominant in all lakes except the most eutrophic, Lake Warden, in which benthic green algae were most abundant. All algal species recorded were known for their wide geographic distribution and their distribution in Australian coastal waters. Characteristically coastal diatom species included Achnanthes brevipes, Achnanthes coarctata, Achnanthes lanceolata var. dubia, Achnanthidium cruciculum, Campylodiscus clypeus, Cyclotella atomus, Cyclotella meneghiniana, Cyclotella striata, Mastogloia elliptica, Mastoglia pumila, Nitzschia punctata and Thalassiosira weissflogii. The inland salt lakes of the Kambalda region form part of an extensive palaeodrainage system, and were much less predictable in terms water regime than lakes in Esperance. Water depth was determined by seasonal variability in rainfall and evaporation, and by summer cyclonic rainfall events that were unreliable from year to year. In addition, rainfall varied spatially within the region. As such, most lakes were classified as intermittent. Two lakes in the region were not classified on the basis of water regime as they were too highly impacted by mining activities including water diversion and impoundment, water extraction and discharge of groundwater. Salinity varied in accordance with drying and filling cycles in the lakes except the most hypersaline as the volume of water received during rainfall events was insufficient to dilute the extensive surface salt crusts they each supported when dry. Salinities recorded in the region ranged from subsaline to hypersaline, and ionic compositions exhibited the same spectrum as seawater.Calcium levels were significantly higher than in lakes from the Esperance region due to weathering of calcium rich sediments, and pH ranged from weakly acidic in the most hypersaline lakes to alkaline in the least saline lakes. All were well mixed in terms of oxygen and temperature. Kambalda salt lakes support distinctive algal communities dominated by diatoms and cyanobacteria that are adapted to intermittent water regimes, extended periods of desiccation and variable salinity. Not surprisingly then, none of the algal taxa recorded from the region were regionally restricted, all noted previously in the literature to have wide geographic distributions, and to be tolerant of a range of physicochemical conditions. Canonical correspondence analysis showed that, of the physicochemical parameters that were investigated in this study, both salinity and pH interacted in determining algal community structure. Both of these attributes were correlated with water depth, which varied according to climatic conditions in a seasonal drying and filling cycle. The general relationship between species richness and pH and salinity, and species diversity and pH and salinity was simple and linear; with increasing pH and salinity, species diversity and species richness decreased. What was less simple, and non-linear, was the nature of the relationship between species richness and diversity and salinity within more narrowly defined ranges of salinity. As salinity increased from <1ppt to 30ppt there was a dramatic reduction in species richness and diversity, then, as salinity increased from 30ppt to 100ppt the rate of decrease slowed. Between 100ppt and 250ppt there was almost no relationship between salinity and species richness and species diversity, but after 250ppt both species diversity and species richness declined markedly.